Spiritual Intelligence In Cross Culture: A Systematic Literature Review And Research Agenda - Rosady, Febry (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The approach used in this study is a systematic literature review (SLR) using Vos Viewer which is related to spiritual intelligence as a reference in "Article Title, Abstract and Keywords" based on the Scopus database from 1964 to 2023. Data analysis was carried out on May 10, 2023 on the Scopus database with a total of 702 articles. The results of secondary data collection carried out on the Scopus database were then processed using VOSviewer to see the relationship between studies. This study offers an in-depth understanding of spiritual intelligence and future research suggestions that are useful for future researchers in building and developing research models related to spiritual intelligence.